Weathering, Drugs and Whack-a-mole: Fundamental and Proximate Causes of Widening Educational Inequity in U.S. Life Expectancy by Sex and Race, 1990-2015. - Geronimus, Arline T. (J Health Soc Behav, 2019)
Discussion of growing inequity in US life expectancy increasingly focuses on the popularized narrative that it is driven by a surge of “deaths of despair.” Does this narrative fit the empirical evidence? Using Census and Vital Statistics data, we apply life-table methods to calculate cause-specific years of life lost between ages 25 and 84, by sex and educational rank, for non-Hispanic blacks and whites in 1990 and 2015. Drug overdoses do contribute importantly to widening inequity for whites, especially men, but trivially for blacks. The contribution of suicide to growing inequity is unremarkable. Cardiovascular disease, non-lung cancers, and other internal causes are key to explaining growing life expectancy inequity. Results underline the speculative nature of attempts to attribute trends in life-expectancy inequity to an epidemic of despair. They call for continued investigation of the possible weathering effects of tenacious high-effort coping with chronic stressors on the health of marginalized populations.